2019
DOI: 10.1038/s41598-019-43023-x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of washing processes of synthetic clothes to microplastic pollution

Abstract: Microplastic pollution caused by washing processes of synthetic textiles has recently been assessed as the main source of primary microplastics in the oceans. Therefore, understanding the effective contribution of the washing process of synthetic clothes to this environmental problem, is of great importance. In this study, wash trials at real scale were performed on commercial clothes by using a household washing machine in order to gain reliable data about the release of microplastics, and to identify possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
195
1
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(262 citation statements)
references
References 30 publications
13
195
1
14
Order By: Relevance
“…4c) fibres. This result confirms that the MPs in the historical period also most likely originated from textiles, because studies have shown that 1900 microfibres could enter the environment when washing an adult garment 39 , and this number was increased to 640,000 to 1,500,000 items•kg −1 in the latest research 40 .…”
Section: Resultssupporting
confidence: 75%
“…4c) fibres. This result confirms that the MPs in the historical period also most likely originated from textiles, because studies have shown that 1900 microfibres could enter the environment when washing an adult garment 39 , and this number was increased to 640,000 to 1,500,000 items•kg −1 in the latest research 40 .…”
Section: Resultssupporting
confidence: 75%
“…In addition to local inputs from visiting vessels and research stations (57), high abundances of fibers in this remote region are probably linked to long-range marine and aerial transport (15), as demonstrated for other anthropogenic contaminants (58), coupled with slow degradation of organic materials in cold-water environments (51). The diameters of our fibers closely matched those of commonly manufactured textile fibers (10,12). Nevertheless, the longest fibers were found in the Mediterranean Sea, probably indicating recent inputs into the basin, being closer to pollution sources and more similar to the length of cotton and rayon fibers freshly released by laundering (10,11).…”
Section: Discussionmentioning
confidence: 52%
“…The causes of this apparent shortage of synthetic fibers in environmental samples are currently unknown, and more research is needed to elucidate this pattern. One plausible explanation is that wool, cotton, and rayon fabrics shed and release more fibers than polyester during laundering (8,9,11,12). However, a crucial factor to understand is the life span of different fiber types in the environment, given the historical dominance of plant and animal fiber use in textiles (2).…”
Section: Discussionmentioning
confidence: 99%
“…Stormwater runoff and wastewater treatment plant (WWTP) effluent also contribute significant microplastic burdens to coastal environments (e.g., Carr et al 2016;Napper and Thompson 2016;Mintenig et al 2017). Microfibers, generally broken down from laundered clothing items or from derelict fishing gear, are the most prevalent form of microplastic in the nearshore environment (Barrows et al 2018;de Falco et al 2019).…”
mentioning
confidence: 99%